Relationship Background to the Economic Family Student Learning Results Elementary School 2 Peukan Pidie - Ismail (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
In the world of family education it is very important to foster life and encourage children to achieve learning outcomes, one of which is the economic condition of students' families. This study seeks to determine the effect of family economic background on student learning outcomes in 5th grade student in Elementary School 2 Peukan Pidie. The approach used in this study is a quantitative approach. While the type of research used is correlation research. The population in this study were all students of 5th grade student in Elementary School 2 Peukan Pidie in the 2019/2020 academic year, namely 33 students. The sampling technique used by the writer is purposive sampling (consideration), the writer conducts purposive sampling based on consideration and obtains 5th grade C as a research sample. Data collection techniques are done using documentation and questionnaires. Data processing uses correlation statistics and t-tests. The results showed that there was a significant relationship between variable X (family economy) and Y (student learning outcomes). The teacher makes an effort in the education of students to get the results of their learning, the parents of students' families help meet their educational needs and encourage their children to achieve good learning outcomes making students a better successor to the nation in the future.